The GE work-out how to implement GE's revolutionary method for busting bureaucracy and attacking organizational problems--fast! - Ulrich, David 1953- (McGraw-Hill, 2002)
Achieve speedy; GE-like outcomes with this guide's organizational methods and strategies. --
Includes bibliographical references and index. - Print version record
Keywords: Organizational change; Industrial organization; Changement organisationnel; Industrie; Organisation, contrôle, etc; BUSINESS & ECONOMICS; Structural Adjustment